Special Relations, Special Obligations, and Speciesism (Bangladesh Journal of Bioethics, 2016)
This paper develops a general account of special relations and special obligations, and uses it as a framework to argue for a modest form of speciesism mitigated speciesism based on an understanding of species co-membership as a thick concept. Mitigated speciesism steers a middle ground between anti-speciesism and crude speciesism. Unlike anti-speciesists, I maintain that species co-membership is a morally relevant special relation, which indeed grounds special obligations among the members of the same species. But unlike crude speciesists, I argue that our special obligations to our fellow human beings do not warrant that we should always count their interests more than comparable interests of non-human animals. Instead, special obligations based on species co-membership are subject to three constraints.